2014
DOI: 10.1186/1559-0275-11-34
|View full text |Cite
|
Sign up to set email alerts
|

The effect of disease on human cardiac protein expression profiles in paired samples from right and left ventricles

Abstract: BackgroundCardiac diseases (e.g. coronary and valve) are associated with ventricular cellular remodeling. However, ventricular biopsies from left and right ventricles from patients with different pathologies are rare and thus little is known about disease-induced cellular remodeling in both sides of the heart and between different diseases. We hypothesized that the protein expression profiles between right and left ventricles of patients with aortic valve stenosis (AVS) and patients with coronary artery diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…Coronary artery and aortic valve disease are associated with specific disease-induced cellular remodeling, since they may exhibit specific cellular proteome and may response differently to ischemic reperfusion injury 9 . Similarly, left and right ventricle may have, as previously demonstrated, different protein profile 9 . Different Authors 10-12 , upon calculating markers of ischemic stress including phosphorylation potential and energy charge, found RIPC to have significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery and aortic valve disease are associated with specific disease-induced cellular remodeling, since they may exhibit specific cellular proteome and may response differently to ischemic reperfusion injury 9 . Similarly, left and right ventricle may have, as previously demonstrated, different protein profile 9 . Different Authors 10-12 , upon calculating markers of ischemic stress including phosphorylation potential and energy charge, found RIPC to have significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, despite a qualitative similarity of the biochemical mechanisms, generating oxygen and carbonyl reactive species (i.e., MAO activity), the elicited scavenging response was quantitatively different in the RV and LV, suggesting that RV might be less equipped than LV to counter oxidative/carbonyl stress. Accordingly, Littlejohns et al [45] showed a more prominent change of protein expression profiles in the diseased RV compared to LV. Lipid peroxidation and protein carbonylation are likely to result from severe oxidative stress contributing to dysfunction of heart contractility [46].…”
Section: Discussionmentioning
confidence: 99%
“…Liquid chromatography‐tandem mass spectrometry (LC‐MSMS) of C‐MSC and MS‐MSC conditioned medium was performed by the University of Bristol Proteomics Facility using a previously described protocol for tandem mass tagging (Thermo Fisher Scientific USA) coupled to liquid chromatography‐mass spectrometry . Values were normalized to a randomly selected control.…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant was collected and stored at −80 C. Protein content was determined using the Qubit Fluorometer and Quant-iT Protein assay kit (Invitrogen USA) according to manufacturer's instructions and diluted to 2 mg/ml. Liquid chromatography-tandem mass spectrometry (LC-MSMS) of C-MSC and MS-MSC conditioned medium was performed by the University of Bristol Proteomics Facility using a previously described protocol for tandem mass tagging (Thermo Fisher Scientific USA) coupled to liquid chromatography-mass spectrometry [31]. Values were normalized to a randomly selected control.…”
Section: Proteomicsmentioning
confidence: 99%